UNLOCKING BUSINESS OPPORTUNITY: DIGITAL LITERACY EMPOWERS KADU'S VILLAGE MSMES, CURUG DISTRICT - Juniarty, Juniarty; Kristiyono, Yokie Radnan; Wijayanti, Cynthia Anna; Harefa, Jeanete Abigail (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Responding to the difficulties of post-pandemic digital transformation, the Business Development Strategy through Digitalization seminar offers Micro, Small, and Medium Enterprises (MSMEs) in Kadu Village, Curug District, Tangerang Regency an empowerment initiative. Aimed to improve participants' knowledge and abilities in digital marketing, the onsite seminar included theoretical insights and practical application that combined Participants' knowledge of digital marketing concepts improved significantly according to evaluation findings; effective social media use for promotion; creative content creation techniques; and the value of branding strategies. Acting as a physical contribution from higher education institutions in supporting inclusive and sustainable local economic development, this seminar effectively bridged the gap between academic theory and the practical needs of MSMEs.